A Survey of Prostate Segmentation Techniques in Different Imaging Modalities - Garg, Gaurav; Juneja, Mamta (Current Medical Imaging, 2018)
Background: Prostate cancer (PCa) is a leading dreadful cancer amid aged men in the United States. During past few decades, a number of studies have been carried out in both medical field and imaging technology for PCa detection and diagnosis. Techniques: Imaging technology-based diagnosis includes TRUS, MRI and CT at the macroscopic level and histological images at the microscopic level. Discussion: To assist novice researchers for a better understanding of prostate segmentation techniques, this article mainly presents the survey of various delineation techniques for prostate pertaining to different modalities i.e. TRUS, MRI and CT, which is an important auxiliary phase in PCa diagnosis. This paper also highlights various PCa grading approaches based on histology imaging with certain gaps that need to address for timely and precise diagnostic recommendations to suppress mortality rates globally. Quantitative/qualitative evaluation and analysis of the existing state-of-the-art segmentation techniques along with their strength and limitations as described in literature is also presented. Conclusion: Prostate delineation is still an open challenge and with progression of technology for identification, medication and follow up of prostate diseases, new prerequisites have to be realized.
Keywords: MRI